IMPLEMENTASI KEBIJAKAN PEMERINTAH TENTANG PENETAPAN KAWASAN TANPA ROKOK, STUDI PADA RUMAH SAKIT UMUM DAERAH UNDATA PROPINSI SULAWESI TENGAH - Zulaeha, Zulaeha (Katalogis, 2015)
This research aims at determining the extent to which the implementation of Smoking Area policy that is implemented within the General Hospital Undata, Central Sulawesi. Non-smoking Area is a place where people are not allowed to smoke in the area, including the public areas, educational facilities, health care facilities, transportation places, children's playground, worship place and workplace. This research uses a qualitative research method and technique of sampling is conducted using purposive sampling with eight informants. The main informant is the director of Regional General Hospital Undata, a specialist, a health worker and five visitors. The results show that the implementation of Smoking Area policy in Regional General Hospital Undata of Central Sulawesi has not run well yet because there are some visitors who smoke in the hospital environment, it is due to the lack of "smoking area" building which is the main facility in the application of non-smoking Area. In addition, due to lack of implementer firmness in conducting the policy, by the lack of sanctions firmness, then it cannot provide a deterrent effect against violators of the rules which makes the implementation of these policies is considered not going well.